Academic freedom: normative ideals, contemporary challenges - Özmen, Elif; Justus Liebig University Giessen (My University, 2024)
There is broad agreement within both science and society about the value of academic freedom. There is disagreement, however, about which forms or degrees, if any, of political and moral regulation might harm or benefit science. Academic freedom, just like free speech in general, has turned into a contentious issue within society as a whole. Competing ideas about science and its social functions, as well as the norms of justice and legitimacy, are debated.
Wissenschaftsfreiheit: Normative Ideale, aktuelle Herausforderungen
Keywords: ddc:100